Application of Deep Breathing Relaxation Technique in Hypertensive Patients to Reduce Blood Pressure - Siska, Siska; Marisa , Dewi Erna; Purbaningsih, Endah Sari; Karlina, Nonok (INDOGENIUS, 2025)
Background & Objective: Globally, the World Health Organization (WHO) estimates that non-communicable diseases cause approximately 60% of deaths and 40% of morbidity worldwide. Based on data from the Cirebon profile (2018), hypertension is the highest health problem in Cirebon, ranging from 22.0% to 26.2%. Based on the data obtained, the highest number of cases of degenerative diseases according to morbidity rates is hypertension, with 37 cases out of 120 elderly individuals. The objective of this study is to analyze the effectiveness of deep breathing relaxation techniques in lowering blood pressure and reducing associated symptoms (such as headaches and sleep disturbances) in hypertensive patients. Method: The research method used a quasi-experiment with a case study approach on a hypertensive patient (Mr. J). The deep breathing relaxation intervention was given once a day for 3 days. Result: The results showed that this technique successfully lowered blood pressure, reduced pain complaints, and improved patients' sleep quality. However, more intensive intervention and a longer duration are needed to achieve optimal results. Conclusion: It is recommended that healthcare professionals, especially nurses, integrate deep breathing relaxation techniques as part of holistic nursing care for patients with hypertension, especially the elderly.